Result of Wine Consumption Survey - Szakál, Zoltán (Acta Agraria Debreceniensis, 2005)
Wine has always played an important role in the Hungarian culture and gastronomy. Today, average wine consumption is about 33 liter per person per year, which figure, comparing with datas in Western Europe, is acceptable. However, cultured wine consumption has begun to develop only in last few years. Consumers, whose knowledges about wines have been widening, demand quality wines. The number of high standard scientific contributions on this subject has risen greatly. But comparisons of them are rather difficult because of adopting different surveying methods. This research has supported and confirmed that wine is a confidental product and previous experience could be an important determining factor during wine-purchasing. Wine is popular as a present, so the nice, elegant look, proper bottles and labels are essential for the higher rate of selling. Further, price-value rate could also be a main factor during the customers’ decision. This survey is a result of a test-research and its methodolical experience will have been used in my following researches.